2020
DOI: 10.1021/acs.jpcc.0c06891
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Behavior of Trimesic Acid with Pentacene at the Liquid–Solid Interface

Abstract: The self-assembly of organic molecules on a solid surface presents a promising route toward the nanoscale-precision construction of functional patterns. In particular, using trimesic acid (TMA) and its self-assembled networks, here we report a template-assisted method to engineer well-ordered structures of pentacene at the organic solvent–graphite interface. Scanning tunneling microscopy revealed that pentacene molecules were merely adsorbed into the TMA chicken-wire (CW) polymorph, and in turn, the template u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Different levels of theory have been employed to identify stable structures and provide insights into the energetics of their formation. Molecular mechanics, , semiempirical quantum-chemical methods, , and density functional theory (DFT) ,, have been employed to obtain the most stable adsorption geometries, normally starting with unit cell parameters obtained from STM observations. DFT is the most reliable method to investigate the energetics of monolayer formation, and it has been used to compare the relative stability of different polymorphs considering the energetic contributions from molecule–substrate interactions as well as hydrogen bonding among the adsorbed molecules. ,, Phase transitions have been investigated with Monte Carlo methods. This approach can predict a range of possible, sometimes coexisting, structures but lacks atomistic detail, and in some studies, the effect of the substrate has been neglected. ,, Molecular dynamics (MD) simulations have been performed to investigate the energetics of epitaxial growth of a supramolecular heterostructure formed by a TMA network deposited on a cyanuric acid/melamine network adsorbed on graphene …”
Section: Introductionmentioning
confidence: 99%
“…Different levels of theory have been employed to identify stable structures and provide insights into the energetics of their formation. Molecular mechanics, , semiempirical quantum-chemical methods, , and density functional theory (DFT) ,, have been employed to obtain the most stable adsorption geometries, normally starting with unit cell parameters obtained from STM observations. DFT is the most reliable method to investigate the energetics of monolayer formation, and it has been used to compare the relative stability of different polymorphs considering the energetic contributions from molecule–substrate interactions as well as hydrogen bonding among the adsorbed molecules. ,, Phase transitions have been investigated with Monte Carlo methods. This approach can predict a range of possible, sometimes coexisting, structures but lacks atomistic detail, and in some studies, the effect of the substrate has been neglected. ,, Molecular dynamics (MD) simulations have been performed to investigate the energetics of epitaxial growth of a supramolecular heterostructure formed by a TMA network deposited on a cyanuric acid/melamine network adsorbed on graphene …”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical and molecular dynamics studies of atomistic models are mainly aimed at determining the energy of epitaxial growth of the TMA phases, assessing their relative thermal stability and disassembly mechanism. [44][45][46][47] In those works it was found that the most stable are the chicken-wire (CW) and filled CW structures. The filled CW structure contains an additional TMA molecule adsorbed in the centre of each hexagon formed by TMA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one can control the mixing behavior of two different molecules physisorbed on the solid surface, and control their nucleation and growth by a stimulus. 113,131,132 Even this stimulus can assist in the formation of a completely new 2D selfassembled structure, as demonstrated by Lee et al, who applied STM to a p-terphenyl-3,5,3′,5′-tetracarboxylic acid (TPTC) molecular building block. 53 In the self-assembly process, some polymeric materials follow dynamic covalent chemistry (DCC), which is of great interest nowadays to obtain self-healing materials.…”
Section: Nanoscale Reviewmentioning
confidence: 97%